Mycotoxins in food: Occurrence, health implications, and control strategies-A comprehensive review - Khan, Rahim (Toxicon (Oxford), 2024)
Mycotoxins are secondary metabolites produced by various filamentous fungi, including Aspergillus, Fusarium, Penicillium, Alternaria, Claviceps, Mucor, Trichoderma, Trichothecium, Myrothecium, Pyrenophora, and Stachybotrys. They can contaminate various plants or animal foods, resulting in a significant loss of nutritional and commercial value. Several factors contribute to mycotoxin production, such as humidity, temperature, oxygen levels, fungal species, and substrate. When contaminated food is consumed by animals and humans, mycotoxins are rapidly absorbed, affecting the liver, and causing metabolic disorders. The detrimental effects on humans and animals include reduced food intake and milk production, reduced fertility, increased risk of abortion, impaired immune response, and increased occurrence of diseases. Therefore, it is imperative to implement strategies for mycotoxin control, broadly classified as preventing fungal contamination and detoxifying their toxic compounds. This review aims to discuss various aspects of mycotoxins, including their occurrence, and risk potential. Additionally, it provides an overview of mycotoxin detoxification strategies, including the use of mycotoxin absorbents, as potential techniques to eliminate or mitigate the harmful effects of mycotoxins and masked mycotoxins on human and animal health while preserving the nutritional and commercial value of affected food products. [Display omitted]